Feeding ecology of the Southern Thorny Skate, Amblyraja doellojuradoi (Pozzi, 1935) on the Argentine Continental Shelf - Delpiani, Gabriela Elina (2013)
The feeding ecology of the Southern Thorny Skate, Amblyraja doellojuradoi, on the Argentine Continental Shelf was evaluated using generalized linear models. A. doellojuradoi preyed mainly on crabs 85.41% index of relative importance (IRI)) and to a lesser extent on polychaetes (4.98% IRI), teleosts (3.28% IRI), isopods (2.03% IRI), other crustaceans (1.52% IRI) and other invertebrates (2.78% IRI). As individuals increased in size, the consumption of crabs also increased and the consumption of polychaetes and other invertebrates decreased. The study area was divided into a northern (368?438S) and a southern (438?508 S) region. Regarding to the latitude of capture, it was observed that A. doellojuradoi mainly fed on crabs in the north and on fishes, isopods and other crustaceans in the south. Females of A. doellojuradoi had a stronger preference for fishes and isopods than males. As to sexual maturity, immatures fed more on polychaetes and other crustaceans than did mature. The ontogenetic change in feeding habits could be attributed to body size and an increasing ability to capture larger prey, rather than to food availability. However, this point cannot be confirmed because little is known about the benthic fauna of this area.